Internal displacement and the promotion of agricultural intensification in Nigeria: Experimental evidence from a fragile setting - Misra, Rewa S.; Bloem, Jeffrey R.; Ambler, Kate; Wagner, Julia; Amare, Mulubrhan (CGIAR System Organization, 2025)
We conduct a field experiment testing information and price discounts on the adoption of a bundle of nutritious and climate-smart agricultural technologies designed to promote agricultural intensification in a fragile setting hosting many internally displaced people (IDPs). We randomly assign farmers in Gombe State, Nigeria to receive vouchers offering either a 50 or 75 percent discount on the technology bundle, along with standard information marketing, or an information-only treatment. Using post-harvest survey data, we estimate the effects of these marketing efforts on technology adoption, complementary input use, crop productivity, and household consumption outcomes. Discounted treatments lead to near universal rates of adoption of the bundle, as well as greater use of bundle components including biofortified seeds (i.e., high iron pearl millet, high iron cowpea, and vitamin A maize) and complementary inputs such as fertilizers and pesticides. Most farmers who purchased the bundle, however, did not adopt the agronomic practices recommended to achieve optimal returns. We do not find significant effects on productivity. We do, however, find evidence of increased consumption of biofortified crop varieties among households offered subsidies. Finally, we find no significant differences between IDP and non-IDP farmers in adoption or investment behavior, suggesting that policy interventions promoting improved agricultural technologies can be effective across both displaced and host populations in fragile settings.